Identification of hypertrophy-modulating Cullin-RING ubiquitin ligases in primary cardiomyocytes - Fischer, Maximillian; Jakab, Moritz; Hirt, Marc N.; Werner, Tessa R.; Engelhardt, Stefan; Sarikas, Antonio (Frontiers in Physiology, 2023)
Cullin-RING ubiquitin ligases (CRL) regulate numerous biological processes in the heart and have been implicated in regulating cardiac hypertrophy. This study aimed to identify novel hypertrophy-modulating CRLs in cardiomyocytes (CM). A functional genomic approach using siRNA-mediated depletion and automated microscopy was employed to screen for cell size-modulating CRLs in neonatal rat CM. Screening hits were confirmed by 3H-isoleucine incorporation. Of 43 targets screened, siRNA-mediated depletion of Fbxo6, Fbxo45, and Fbxl14 resulted in decreased cell size, whereas depletion of Fbxo9, Fbxo25, Fbxo30, Fbxo32, Fbxo33, Cullin1, Roc1, Ddb1, Fbxw4, and Fbxw5 led to a markedly increased cell size under basal conditions. In CM stimulated with phenylephrine (PE), depletion of Fbxo6, Fbxo25, Fbxo33, Fbxo45, and Fbxw4 further augmented PE-induced hypertrophy. As a proof-of-concept, the CRLFbox25 was analysed by transverse aortic constriction (TAC) resulting in a 4.5-fold increase in Fbxo25 protein concentrations compared to control animals. In cell culture, siRNA-mediated depletion of Fbxo25 resulted in a ~ 37% increase in CM cell size and ~ 41% increase in 3H-isoleucine incorporation. Depleting Fbxo25 resulted in upregulation of Anp and Bnp. In summary, we identified 13 novel CRLs as positive or negative regulators of CM hypertrophy. Of these, CRLFbox25 was further characterized, as a potential modulator of cardiac hypertrophy.